Modelling the impacts of climate change and air pollutants on the agricultural production yields in Malaysia using Random-Effects Error Components Regression model - Chuan, Zun Liang; Fam, S. F.; Lee, Q. H.; Kok, J. S.; Azam, M. N. B. M. (Penerbit UMP, 2022)
The occurrence of climate change is attributable to anthropogenic emissions of greenhouse gases (GHG) which have affected the C3 plants’ agricultural production yields in past decades. Therefore, this article aims to model the linear association among these C3 plants’ agricultural production yields with several climatic and non-climatic explanatory variables using one-way random-effects error components regression model. To be congruent with the main objective of this study, the balanced longitudinal dataset period 1980 to 2018 under big data was acquired. The analysis results revealed that merely maximum temperature (